Mapping Trends on Employee Performance and Work Environment: A Bibliometric Analysis - Dzakiah Azizah Luthfiyana; Retno Widowati; Arni Surwanti (CV. Syntax Corporation Indonesia, 2024)
Employee performance and work environment are two key elements in the success of an organization. The relationship between employee performance and the work environment has become a major focus for many organizations to improve productivity, employee satisfaction, and overall organizational performance. This study aims to determine the development of research with the theme Employee Performance and Work Environment in the range of 2014 to 2023 through the help of the Vosviewers application in visualizing data. The method used in this study is qualitative research with a literature study approach. As for the data found, 98 documents were obtained and analyzed. These datasets are converted to CSV format, BibTeX, and RIS format and imported into bibliophilia for bibliometrics and analysis. The results showed that 2023 is the year with the highest number of publications on the topic of Employee Performance and Work Environment. Indonesia is the country that influences scientific publications the most. Samani, S.A. is the most prolific writer with 3 documents in the field of Employee Performance and Work Environment. Great potential for further research in areas such as Compensation, leadership, training, work-life balance, and work engagement, which still has the potential to be explored more deeply in the context of Employee Performance and Work Environment.